Fibromuscular dysplasia of internal carotid artery - Yu. I. Kuzyk (Zaporozhye State Medical University, 2015)
Fibromuscular dysplasia (FMD) is the disease of arteries of medium and small caliber with unknown etiology. Aim. To determine the features of pathomorphological picture of carotid FMD operating material of 134 patients operated on for symptomatic FMD was studied using methods of light microscopy and histochemical methods. Methods and results. It was established that specific macroscopic feature of FMD of carotid arteries are multiple saccular aneurysms, creating a picture of the «string of beads». A typical pathomorphological variant of FMD is medial fibroplasia with total fibro-muscular transformation and complete loss of elastic. Conclusion. This indicates that FMD is a non-inflammatory disease, based on the muscular and connective tissue transformation, probably of congenital genesis.